Multi Drug Resistance and Biofilm Production among Staphylococci Isolates from Clinical Samples at a Tertiary Care Hospital in Kathmandu, Nepal (Tribhuvan University Journal of Microbiology, 2022)
Objectives: The purpose of the study was to determine multidrug resistance and biofilm production among Staphylococcus isolates from clinical samples at Nepal Armed Police Force Hospital, Kathmandu.Methods: A hospital based cross sectional prospective study was conducted at Department of Microbiology, Nepal Armed Police Force Hospital, Balambu, Kathmandu from February to July 2022. A total of 1813 clinical samples were collected and processed in microbiology laboratory. Through cultural and biochemical analysis, Staphylococcus spp. were isolated and identified, and the Kirby-Bauer disc diffusion method was used to determine multidrug resistant among isolates. While the Tissue Culture Plate method was employed to detect Staphylococcus spp. that produce biofilm.Results: Out of 1813 clinical samples, 304 (16.7%) exhibited bacterial growth; of these, 135 (44.4%) were Staphylococcus spp, among which 119 (88.1%) were S. aureus, 16 (11.8%) were coagulase negative Staphylococci (CONS) and 114 (84.4%) were MDR. Eighty-one (68.1%) of the 119 S. aureus isolates were methicillin resistant, and 11 (68.8%) of the 16 CONS were also resistant to the methicillin. Eighteen (13.3%) of the 135 Staphylococcus spp. were detected to be strong biofilm producers, 30 (22.2%) moderate, and 87 (64.4%) non or weak biofilm producers. Both biofilm producers and biofilm non-producers were found to be resistant against Ampicillin and Azithromycin.Conclusion: The study reveals higher percentage of MDR among Staphylococcus spp, indicating the need to discourage self-medication, insufficient or over – medication. Moreover, the high rates of biofilm development in MDR Staphylococcus spp and MRSA underscores the need for monitoring of biofilm producers.